Capturing The 'Pioneering Minds' Via Human Capital: The Impact On Innovative Performance Of Malaysian Smes - Abdul Halim, Hasliza; Ahmad, Noor Hazlina; T. Ramayah, T. Ramayah; Taghizadeh, Seyedeh Khadijeh (Asian Academy of Management (AAM), 2016)
To cultivate “pioneering minds” is extremely important especially in the eﬀort to shift Malaysia towards innovation-centered economy. The Malaysian government is confdent of achieving the target provided that the human capital is leveraged in ensuring innovation at the highest level particularly among Small and Medium Enterprises (SMEs). Nevertheless, only few studies have considered human capital as a factor that mediates the eﬀects of other variables on innovation. Therefore, this paper aims at investigating on how human capital dimensions namely uniqueness, value and pro-activeness will be leveraged by pro-innovativeness organisational architecture dimensions that is allocation for free time, work discretion, rewards, and tolerance for risk taking in order to achieve innovative performance. A structured study instrument was used for data collection purpose. A total of 1000 active SMEs were selected via simple random sampling from Malaysia Small and Medium Enterprises Directory 2011/12. A total of 263 SMEs responded to the questionnaire. However, a total of 262 usable questionnaires were thus secured for analysis. The analysis was then conducted via Partial Least Squares (PLS) structural equation modeling (SEM). The results showed several interesting fndings: (a) rewards has an inﬂuence on the uniqueness, value and pro-activeness of human capital; (b) tolerance towards risk taking has an inﬂuence on human capital (uniqueness, value and pro-activeness; (c) uniqueness Hasliza Abdul Halim et al. 106 of human capital has an inﬂuence on innovative performance and (d) uniqueness of human capital mediated the relationship between tolerance for risk taking and innovative performance. The fndings suggest that SMEs should put more focus on the reward system and tolerance for risk taking in order to encourage and enhance the 'pioneering mind' which in turn may increase innovative performance of SMEs.